Validation Of A Three-Phase Cascaded Multilevel Inverter Based On Newton Raphson (N.R.) - Mohammed, Rasheed; Rosli, Omar; Afiqah, Sabari; Marizan, Sulaiman (Indian Society For Education And Environment & Informatics Publishing Limited, 2016)
This paper discusses the configuration three-phase Cascaded H-Bridge Multilevel Inverter (CHBMLI) based on Newton Raphson (N.R.) method to produce obtain five-levels of output voltage by reduce Total Harmonic Distortion (THD). Method: The proposed method had been comprised of 5-level multilevel inverter, while the control system was based on the Newton Raphson (N.R.) method. Moreover, the main purpose of the research was to investigate the effectiveness of the proposed method by using NR for harmonic analysis in high voltage electrical distribution system. Besides, the optimization of the controller based on modulation indexes was employed in order to optimize and non-optimize the switching angle of the CHBMLI for different modulation indexes. Findings: An inverter is used to convert DC power generator from the DC supply into AC power. The five-level inverter resulting in increased voltage levels of the output waveform. As the levels of output waveform increase, the percentage of THD reduced and switching losses decreased to improves power quality have been done compared with conventional three phase Dc supply connected PWM cascaded H-bridge multilevel inverter. Based on Newton Raphson (N.R.) five-level of output voltage is produced by the inverter zero, +1/2Vdc, +Vdc, -1/2Vdc and –Vdc. Improvements: Apart from that, the proposed scheme was modelled with MATLAB software and the Simulation results were verified via hardware experimental by using Digital Signal Processing (DSP) TMS320F2812. The experimental results showed that the proposed method had been effective in verifying the NR control in terms of Total Harmonic Distortion (THD).